Comparative Study on the Proximate and Amino Acids Levels in Selected Edible Mushroom Species - Adebisi, Arowora Kayode; Joseph, Iornenge Terungwa; Adams, Idris Habiba; Mohammed, Ikrimah Usman; David, Bando Christopher; Efoseh, Danlami; Umaru, Isaac John (Darul Yasin Al Sys, 2025)
Mushrooms represent an ancient group of heterotrophic organisms classified under Thallophytae, and based on their chemical composition and utility, they are broadly categorized as edible or poisonous. Edible mushrooms can further be divided into wild and cultivated types. This study compares the amino acid profiles and proximate compositions of two edible mushrooms, tea tree mushroom (Agrocybe aegerita) and oyster mushroom (Pleurotus ostreatus), collected from Takum Local Government Area of Taraba State, Nigeria. Freshly harvested samples were air-dried for three days, pulverized, and subjected to amino acid analysis using isocratic high-performance liquid chromatography (HPLC) and proximate analysis following standard protocols from the Association of Official Analytical Chemists (AOAC). Results showed that Agrocybe aegerita exhibited higher concentrations of amino acids compared to Pleurotus ostreatus, with a non-significant decrease (p > 0.05) observed in Pleurotus ostreatus for essential and non-essential amino acids including lysine, methionine, threonine, isoleucine, leucine, phenylalanine, valine, tryptophan, histidine, arginine, serine, cysteine, tyrosine, alanine, aspartic acid, glutamic acid, glycine, and proline. Conversely, Pleurotus ostreatus demonstrated slightly higher values in proximate components such as carbohydrate, fiber, ash, and moisture, whereas Agrocybe aegerita showed higher but non-significant values in protein, fat, and energy content. The study concludes that Agrocybe aegerita is nutritionally superior in terms of amino acid composition, while Pleurotus ostreatus is marginally better in proximate nutritional content, supporting their complementary roles in dietary applications.